Strengthening laboratory surveillance of antimicrobial resistance in South East Asia. (5th September 2017) - Shah, Aparna Singh; Karunaratne, Kumudu; Shakya, Geeta; Barreto, Ismael; Khare, Shashi; Paveenkittiporn, Wantana; Wangchuk, Sonam; Tin, Htay Htay; Muhsin, Milza Abdul; Aung, Lin; Bhatia, Rajesh; Srivastava, Rahul; et al.
Abstract : Aparna Shah and colleagues call on South East Asian countries to invest in national networks of laboratories for robust and standardised surveillance of antimicrobial resistance